2019
DOI: 10.1016/j.tcm.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary look at pericardiocentesis

Abstract: Percutaneous drainage is the default strategy for evacuating a pericardial effusion. A pericardiocentesis can be necessary or required in a wide variety of clinical settings ranging from urgent tamponade to relieve in iatrogenic hemorrhagic effusions in the electrophysiology or catheterization room, to planned diagnostic procedures in patients with suspected or known malignancy or infections. With the help of several procedural improvements over the past decades, echocardiography and fluoroscopy-guided percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Pericardiocentesis, either echocardiographically or fluoroscopically guided, is an effective treatment modality performed either emergently or electively for a myriad of indications ranging from sizeable pericardial effusion resistant to medical management to diagnostic taps for unknown etiology . Pericardiocentesis may be associated with minor and major complications that include but are not limited to: pneumothorax, catheterization of the wrong site and/or organ, cardiac puncture, coronary artery laceration, massive hemorrhage, and intra‐procedural death .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericardiocentesis, either echocardiographically or fluoroscopically guided, is an effective treatment modality performed either emergently or electively for a myriad of indications ranging from sizeable pericardial effusion resistant to medical management to diagnostic taps for unknown etiology . Pericardiocentesis may be associated with minor and major complications that include but are not limited to: pneumothorax, catheterization of the wrong site and/or organ, cardiac puncture, coronary artery laceration, massive hemorrhage, and intra‐procedural death .…”
Section: Introductionmentioning
confidence: 99%
“…Pericardiocentesis, either echocardiographically or fluoroscopically guided, is an effective treatment modality performed either emergently or electively for a myriad of indications ranging from sizeable pericardial effusion resistant to medical management to diagnostic taps for unknown etiology. 1,2 Pericardiocentesis may be associated with minor and major complications that include but are not limited to: Note: Table 1 showing the observed baseline differences between patients who underwent pericardiocentesis with cardiac procedures during hospitalization versus patients who underwent pericardiocentesis in hospitalizations without procedures. and an interventional procedure at the same hospitalization versus those who did not (Tables S1 presents the corresponding ICD-9 codes used in the current article, as well as a comparison between pericardiocentesis and surgical pericardial interventions).…”
Section: Introductionmentioning
confidence: 99%
“…Several other observational studies demonstrated that the parasternal approach was superior to the traditional subxiphoid approach. [18][19][20][21] In our study, the parasternal approach had the lowest predicted complication rate with a shorter mean skin-to-pericardial fluid distance compared to the subxiphoid approach. Our study suggests that the parasternal approach is superior to the subxiphoid approach even under ultrasound guidance.…”
Section: Discussionmentioning
confidence: 49%
“…Pericardiocentesis is an important procedure for treating cardiac tamponade, and echocardiography-guided pericardiocentesis has been recognized as a safe and feasible technique that has low complication rates. However, it can still be a high-risk procedure in inexperienced hands and/or an emergency setting [1]. Here we report a case of right coronary artery perforation secondary to pericardiocentesis for cardiac tamponade.…”
Section: Introductionmentioning
confidence: 93%